The formation pattern, causes, and governance of network public opinion on university emergencies - Gao, Xiaoning; Li, Zhuoya; Zhang, Ke; Bi, Chongwu (Frontiers in Public Health, 2024)
Background: University emergencies, garnering significant public attention and shaping network opinions, pose a crucial challenge to universities' management and societal stability. Hence, network public opinion on university emergencies is a vital issue. Nevertheless, the underlying mechanism has not been fully explored and cannot be efficiently controlled. study aims to explore the formation pattern of network public opinion on university emergencies, analyze its causes, and provide scientific governance strategies for coping with this issue. Methods: Based on a sample set of 204 cases from the Zhiwei Data Sharing Platform, this study classifies network public opinion on university emergencies into six types and visually analyzes their characteristics: time distribution, subject, duration, and emotion. By integrating the theory of the network public opinion field, this study develops a network public opinion field model of university emergencies to reveal its formation pattern. Furthermore, it analyzes the causes of network public opinion on university emergencies from the perspective of the public opinion lifecycle and proposes corresponding governance strategies. Results: The sample consisted of 304 cases of real-life public opinion, and the visualization results show that: public opinion on mental health and teacher-student safety constitute the predominant types, accounting for 83.3%. High-occurrence subjects are public universities (88.24%) and students (48%). The most frequent months are July and December. 90.20% of the public opinions have a lifespan of less than 19 days, with impact index ranging from 40 to 80. The public's emotional response to different types of public opinion varies, with negative emotions dominating. Conclusion: This study provides novel insights for understanding their formation and dissemination. It also provides practical implications for relevant departments to govern network public opinion on university emergencies.